GREEN MARKETING ANALYSIS IN SKINCARE BUSINESS: A CASE STUDY OF GARNIER AND NPURE (Journal of Technology and Operations Management, 2025)
Garnier and Npure, two skincare brands, utilize green marketing as a core business strategy. This study employed descriptive quantitative analysis methods with non-probability sampling techniques and SEM PLS to investigate the two skincare brands. The study aimed to identify the characteristics of consumers and green marketing practices for these brands, analyze the effect of green marketing on purchase intention through brand image, and develop recommendations to increase purchase intention and brand image through green marketing. The findings reveal that green marketing has a positive and significant effect on both purchase intention and brand image for Garnier and Npure. Furthermore, brand image is shown to have a positive and significant effect on purchase intention and partially mediates the relationship between green marketing and purchase intention for these brands.